2020
DOI: 10.3171/2019.7.spine19630
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rod fracture rates in long spinal deformity constructs after transforaminal versus anterior lumbar interbody fusions: a single-institution analysis

Abstract: OBJECTIVEPseudarthrosis is a common complication of long-segment fusions after surgery for correction of adult spinal deformity (ASD). Interbody fusions are frequently used at the caudal levels of long-segment spinal deformity constructs as adjuncts for anterior column support. There is a paucity of literature comparing rod fracture rates (proxy for pseudarthrosis) in patients undergoing transforaminal lumbar interbody fusion (TLIF) versus anterior lumbar interbody fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
18
2
Order By: Relevance
“…In Adogwa's study, they reported that revision surgery was required in 14 (51.9%) out of 27 patients with metal failure in the TLIF cohort and in four (36.3%) of 11 patients with metal failure in the ALIF cohort. 28 Daniels et al 39 found that 38 (9.5%) of 402 patients with radiographically apparent solid fusion suffered a broken rod, suggesting the radiographically apparent fusion mass may not be strong for repetitive mechanical stress in a long-term period. Another study reported rod fracture despite a CT scan showing fusion among spinal tumor patients after total en bloc spondylectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In Adogwa's study, they reported that revision surgery was required in 14 (51.9%) out of 27 patients with metal failure in the TLIF cohort and in four (36.3%) of 11 patients with metal failure in the ALIF cohort. 28 Daniels et al 39 found that 38 (9.5%) of 402 patients with radiographically apparent solid fusion suffered a broken rod, suggesting the radiographically apparent fusion mass may not be strong for repetitive mechanical stress in a long-term period. Another study reported rod fracture despite a CT scan showing fusion among spinal tumor patients after total en bloc spondylectomy.…”
Section: Discussionmentioning
confidence: 99%
“…All these patients went on to have solid L5-S1 fusion on CT scan and have not had a revision. This failure rate again is low compared to published reports of rod failure with open surgery [50][51][52][53][54][55][56][57][58][59][60]. This may be due to two reasons.…”
Section: Discussionmentioning
confidence: 58%
“…Anterior and transforaminal interbody fusion procedures at the caudal levels of long spinal deformity constructs are associated with low bilateral rod fracture rates and do not differ in the rate of revision surgery between the two groups [15]. Further, the prevalence of rod fractures is not significantly different between anterior and transforaminal groups [15]. Although we performed anterior reconstruction for patients with anterior bone defects using the posterior approach, no failure occurred in most instances.…”
Section: Discussionmentioning
confidence: 84%
“…These results showed that refracture occurs even after anterior column reconstruction. Anterior and transforaminal interbody fusion procedures at the caudal levels of long spinal deformity constructs are associated with low bilateral rod fracture rates and do not differ in the rate of revision surgery between the two groups [15]. Further, the prevalence of rod fractures is not significantly different between anterior and transforaminal groups [15].…”
Section: Discussionmentioning
confidence: 92%